30.6k views
12 votes
F(x) = 2x+6, g(x) = 3² findf(g (-3))​

User Chante
by
4.9k points

2 Answers

8 votes

Explanation:

If F(x) = 2x+6, g(x) = 3² findf(g (-3))

Solution

f(g (-3)) = 2x+6(3²(-3)) = 2x+6(3×3(-3))

= 2x+6(-27) = 54x-162 = 54x = 162

54/54x = 162/54

x = 3

User Nelsonda
by
5.2k points
6 votes

Answer:


f(g(-3)) = 24

Explanation:

➨ Rearrange/Simplify the equations


F(x)=2x+6\\g(x)=9

➨ Find
f(g(-3))


g(-3)=9 ➩ All x-values have same y-values ➩ Constant Function

Substitute
g(-3) = 9 in the f(x)


f(g(-3)) = f(9)\\f(9)=2(9)+6\\f(9)=18+6\\f(9)=24\\f(g(-3)) = 24

Thus, the answer ➩
f(g(-3)) = 24

User Sashaaero
by
5.2k points